Phylogenetic analysis of 23 accessions of Indonesian banana cultivars based on Internal Transcribed Spacer 2 (ITS2) region - Karlia Meitha; Intan Fatmawati; Agus Sutanto; Sigit Nur Pratama; Husna Nugrahapraja; Ketut Wikantika; Fenny Martha Dwivany (Universitas Gadjah Mada, 2020)
Pisang Kepok (Musa spp. [ABB ’Saba’ subgroup]) has several unique characteristics, such as tolerance to drought and Fusarium Foc (TR4) disease. Currently, the genetic diversity of Pisang Kepok in Indonesia is not well identified, although it is widely cultivated. Information on genetic diversity is essential for developing breeding strategies to achieve efficient cultivar improvement in the future. Aims of this research were to analyze the genetic variation of Pisang Kepok from some islands in Indonesia and to determine the genetic relationship between Pisang Kepok and other accessions banana cultivars based on ITS2 region, as a basis for future research in improving banana quality through molecular breeding. We have conducted the multiple sequence alignment and built the phylogenetic tree analysis using the Bayesian Inference Phylogeny method of one million generations (ngen = 1,000,000). The ITS2 region showed two clade ingroups: first clade consists of banana with B genome (balbisiana), while the second clade consists of banana with only A genome (acuminata). In general, all accessions of Pisang Kepok cultivars were clustered in the B genome of bananas cultivars. In addition, the ITS2 sequences and secondary structures among Pisang Kepok from various regions are identical, suggesting that there was no genetic variation in the ITS2 region of Pisang Kepok from multiple areas in Indonesia.